Pengaruh Kualitas Website Terhadap Kepuasan Dan Loyalitas Mahasiswa STMIK Kadiri - In wahyu widodo; Sri Wahyuni Mega; Imam Baehaqi (Otonomi, 2020)
This research was conducted to examine the effect of website quality on student satisfaction and loyalty at the Sekolah Tinggi Manajemen Informatika dan Komputer Kadiri (STMIK Kadiri). This research uses a quantitative method with a descriptive approach. Data collection by distributing questionnaires to STMIK Kadiri students who are still active, totaling 120 people from 2017 to 2019. The analysis technique uses path analysis and hypothesis testing. For data processing using the program Eviews and IBM SPSS statistics.